2017
DOI: 10.1089/lap.2016.0204
|View full text |Cite
|
Sign up to set email alerts
|

Learning Curve Analysis of Laparoscopic Kasai Portoenterostomy

Abstract: A surgeon is able to become more experienced after performing approximately 40 laparoscopic Kasai Portoenterostomys.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 11 publications
0
3
1
3
Order By: Relevance
“…The 50 cases of learning curve in our study was more than that reported by Li et al [ 19 ]. The authors drew the conclusion that without the usage of Cumulative sum analysis for ORT and Kaplan–Meier analysis for SNL.…”
Section: Discussioncontrasting
confidence: 41%
“…The 50 cases of learning curve in our study was more than that reported by Li et al [ 19 ]. The authors drew the conclusion that without the usage of Cumulative sum analysis for ORT and Kaplan–Meier analysis for SNL.…”
Section: Discussioncontrasting
confidence: 41%
“…This was especially apparent for Kasai portoenterostomy, esophageal atresia repair, and pyloromyotomy. For example, during the learning curve for Kasai portoenterostomy in the presented series, the first-year native liver survival rate was 16 to 35% lower, 17,18 which translates to 8 to 14 patients requiring a liver transplant that potentially could have been avoided had the learning curve been completed already. Similarly, two to five patients undergoing n/a n/a n/a n/a n/a n/a…”
Section: Discussionmentioning
confidence: 85%
“…Лапароскопические операции позволяют минимизировать травматичность данной процедуры, сокращая использование наркотических анальгетиков и время пребывания ребенка на ИВЛ в послеоперационном периоде, также раньше начинается энтеральная нагрузка [46,48,49,50]. По своей эффективности лапароскопические операции не уступают открытым операциям [46] и одним немаловажным фактом является то, что количество хирургических осложнений после данной методики меньше, чем после открытых операций [49,51] Про расширенную портоэнтеростомию Davenport at al. [15,58] сообщают, что радикальное иссечение всех внепеченочных желчных протоков и широкая портоэнтеростомия, охватывающая все резецированные участки, в которые возможно открываются необлитерированные желчные протоки, являются обязательными, несмотря на трудоемкую и кропотливую технику выполнения.…”
Section: лечение баunclassified
“…При III типе атрезии желчных ходов годичная выживаемость находится в диапазоне от 50% до 76,2% [51,53,57], частота встречаемости холангитов в раннем послеоперационном периоде варьирует от 18,7% до 43,7%, а 5-ти летняя выживаемость составляет 47,1% [43].…”
Section: анатомо-морфологические особенности баunclassified